Analysis of Immunological Characteristics and Genomic Alterations in HPV-Positive Oropharyngeal Squamous Cell Carcinoma Based on PD-L1 Expression - Xu, Sheng-ming; Shi, Chao-ji; Xia, Rong-hui; Wang, Li-zhen; Tian, Zhen; Ye, Wei-min; Liu, Liu; Liu, Shu-li; Zhang, Chun-ye; Hu, Yu-hua; Zhou, Rong; Han, Yong; et al. (Frontiers in Immunology, 2022)
Programmed death-ligand 1 (PD-L1) expression has been approved as an immune checkpoint inhibitor (ICI) response predictive biomarker; however, the clinicopathological and molecular features of HPV-positive oropharyngeal squamous cell carcinoma [HPV(+)OPSCC] based on PD-L1 expression are not well studied. We aimed to characterize clinicopathological, tumor immune microenvironmental, and molecular features of HPV(+)OPSCC with different PD-L1 expression scored by combined positive score (CPS). A total of 112 cases were collected from 2008-2021 and received PD-L1 and CD8 immunohistochemistry (IHC) staining. 71 samples received DNA sequencing out of which 32 samples received RNA sequencing for immune-related gene alterations or expression analysis. The 32 samples were also subjected to analysis of CD20, CD4, CD8, CD68, Foxp3 and P16 by multiplex immunofluorescence (mIF) staining, and the immune markers were evaluated in the tumor body (TB), tumor margin (TM) and normal stroma (NS) regions separately. Our results showed that of 112 HPV(+)OPSCC tumors, high(CPS≥20), intermediate(1≤CPS<20), and low(CPS<1) PD-L1 expression was seen in 29.5%, 43.8% and 26.8% cases respectively. Non-smoking patients and patients with tumors occurring at the tonsils or having rich lymphocytes infiltration had significantly higher PD-L1 expression. Patients with CPS≥20 had significantly higher tumor mutation burden (TMB, p=0.0058), and PD-L1 expression correlated significantly with CD8+ T cells infiltration, which were ample in tumor regions than in NS in mIF. CD20+, CD4+, CD68+, Foxp3+CD4+ cells were demonstrated to infiltrate higher in TM while CD20+ and CD68+ cells were also enriched in NS and TB regions respectively. However, none of them showed correlations with PD-L1 expression. ARID1A, STK11 alterations were enriched in the low PD-L1 group significantly, while anti-viral immune associated APOBEC mutation signature and immune-related genes expression such as XCL1 and IL11 were positively associated with PD-L1 expression (p<0.05). This is a comprehensive investigation revealing immune and molecular features of HPV(+)OPSCC based on PD-L1 expression. Our study suggested that 73.2% of HPV(+)OPSCC patients may benefit from immunotherapy, and high PD-L1 expression reflects immune-active status of HPV(+)OPSCC accompanied by higher immune effect factors such as TMB, CD8+ cytotoxic T cells and immune-related genomic alterations. Our study offers valuable information for understanding the immune features of HPV(+)OPSCC.